A Malaysian Outcome-Based Engineering Education Model: The Implementation and Challenges in Future - Sam*, ManKeong; Soong*, Cai Juan; Kok, Ching Wen (INTI International University, 2020)
Malaysia is one of the signatories member of the Washington Accord as well as the Engineering Accreditation Council (EAC) in the country. The change to an Outcome-Based Learning (OBE) is an entitle transformation mode where students are educated, assessed and graduated. Even though the EAC’s 1999 issued guidebook listed 12 graduate attributes, but yet less effort to ensure engineering education appreciate and implement it. In 2000, the Malaysian Engineering Education Model also precede for engineering education to adopt OBE but the spirit of MEEM was not entirely comprehended and there was no force to obey to the recommendations. Since 2004, Malaysia Higher Education Ministry has adopted the OBE to emerge with few engineering education providers leading the way. Although many educational institutes have prefer in implementing OBE curriculum to deliver Engineering Education, but yet challenging and tedious tasks to implement it successfully. Hence, the aim of this study is to scrutinize a variety of challenges encountered by instructors in implementing the OBE in conveying technical subjects in tertiary university. A preliminary test of OBE is conducted in this study. Data are collected from 13 instructors from private university through questionnaire survey as well as interviews. Data collected are analysed and exploiting both descriptive statistics and statistical tests to delineate the primary challenges. Consequently, the novelty findings established significantly in OBE implementation especially these vital facts should be right direction and aid to unlock frontiers for preparing instructors in facing future challenges which impeded the effective implementation of OBE curriculum in teaching and learning in tertiary university.